Active Learning to Improve Self-Confidence and Decision-Making Skills Through the Use of Hotel Simulation. Issue 3 (3rd July 2019) - Ampountolas, Apostolos; Shaw, Gareth; James, Simon
ABSTRACT: This study evaluated the use of hotel simulation learning and how it promotes users' confidence as a decision-making tool. Given the challenges of preparing students for the service industry, it enables them to make hypothetical decisions based on real-life scenarios. The perceived learning experience can enhance students' critical thinking ability to manipulate different operational strategies. Data were collected from 202 students who attended hospitality management programs in Switzerland, the United States, and the United Kingdom. A series of regression analyses were conducted to test how confident the students were in their ability to make decisions. This article compares perceived self-confidence and the development of decision-making skills between undergraduate and postgraduate students. The students improved their confidence and thus their decision-making skills relating to day-to-day operations. In addition, confidence was more effectively valued as a relevant norm among undergraduate than postgraduate students in developing critical and analytical decision skills.